Triiodothyronine levels in athyreotic pediatric patients during levothyroxine therapy - Baran, Julia; Isaza, Amber; Bojarsky, Mya; Alzoebie, Lama; Song, Minkeun; Halada, Stephen; Sisko, Lindsay; Gonzales, Stephanie; Mostoufi-Moab, Sogol; Bauer, Andrew J. (Frontiers in Endocrinology, 2024)
Objective Levothyroxine (LT4) monotherapy is the current recommended approach for treating pediatric patients post-total thyroidectomy (TT) based on the assumption that peripheral conversion of thyroxine (T4) to triiodothyronine (T3) normalizes thyroid hormone levels. In adults, approximately 15% of post-TT patients on LT4 monotherapy have altered T4:T3 ratios with ongoing debate in regard to the clinical impact with respect to health-related quality of life (hrQOL). The ability to normalize T3 and T4 levels on LT4 monotherapy for pediatric patients’ post-TT is important but not previously described. This study reports data on T3 levels in athyreotic pediatric patients to determine if a similar cohort of patients exists on LT4 monotherapy targeting normalization of TSH (LT4 replacement) or suppression (LT4 suppression). Methods Thyroid function tests (TFTs) were retrospectively extracted from medical charts for patients <19 years old who underwent TT for definitive treatment of Graves’ disease (GD) or differentiated thyroid cancer (DTC) between 2010–2021. LT4 dosing was selected to normalize the TSH in GD patients (LT4 replacement) or suppress TSH in DTC patients (LT4 suppression). Pre- and post-surgical TSH, T3 and T4 levels were compared. Results Of 108 patients on LT4 replacement (n=53) or LT4 suppression (n=55) therapy, 94% (102/108) of patients demonstrated T3 levels in the normal range post-TT. However, the majority of patients on LT4 replacement (44/53; 83%) and LT4 suppression (31/55; 56%) displayed post-TT T3 levels in the lower half of the normal range despite 50% (22/44) and 48% (15/31) of these patients, respectively, having post-TT fT4 levels above the upper limit of the normal range. Conclusion A significant number of pediatric patients do not achieve similar T3 and T4:T3 levels pre- and post-TT. Future multi-center, prospective studies evaluating LT4 monotherapy in comparison to combined LT4/LT3 therapy are warranted to determine the potential clinical impact of altered T3 levels in athyreotic pediatric patients.